ChemInform Abstract: Rhodium‐Catalyzed Asymmetric Hydroarylation of 3‐Pyrrolines Giving 3‐Arylpyrrolidines: Protonation as a Key Step. Issue 3 (21st January 2014) - So, Chau Ming; Kume, Satoshi; Hayashi, Tamio
Abstract The highly enantioselective and high yielding title reaction provides an easy and efficient access of 3‐arylpyrrolidines, compounds with potentially biological activity, under neutral conditions.